1990
DOI: 10.1111/j.1469-8137.1990.tb00528.x
|View full text |Cite
|
Sign up to set email alerts
|

The association of Morchella rotunda (Pers.) Boudier with roots of Picea abies (L.) Karst

Abstract: SUMMARYA histo-cytological study of Norway spruce [Picea abies (L.) Karst.] roots connected to ascocarps of Morchella rotunda (Pers.) Boudier revealed that hyphae of morel were associated with all parts of the root system. The main suberized roots were surrounded by a mycelial sheath. The finer rootlets were enveloped by a cottony mycelium and their absorbing root tips were found to be ectomycorrhizal. Morel hyphae also invaded the oldest parts of a heterobasidiomycete ectomycorrhiza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…These fungi have been considered by other researchers to be early successional fungi found in nursery-grown conifers and following fire (Wilcox et al 1974(Wilcox et al , 1983Wilcox 1984, 1985;Mikola 1965;Lahio 1965;Danielson 1982Danielson , 1984Scales andPeterson 1991, Visser 1995). This correlates well with the production of abundant ascocarps of known biotrophic fungal genera such as Morchella (Buscot and Kottke 1990), Gyromitra, Sphaerosporella, and Tricharina present at our research sites throughout the summer of 1989. This correlates well with the production of abundant ascocarps of known biotrophic fungal genera such as Morchella (Buscot and Kottke 1990), Gyromitra, Sphaerosporella, and Tricharina present at our research sites throughout the summer of 1989.…”
Section: Discussionsupporting
confidence: 78%
“…These fungi have been considered by other researchers to be early successional fungi found in nursery-grown conifers and following fire (Wilcox et al 1974(Wilcox et al , 1983Wilcox 1984, 1985;Mikola 1965;Lahio 1965;Danielson 1982Danielson , 1984Scales andPeterson 1991, Visser 1995). This correlates well with the production of abundant ascocarps of known biotrophic fungal genera such as Morchella (Buscot and Kottke 1990), Gyromitra, Sphaerosporella, and Tricharina present at our research sites throughout the summer of 1989. This correlates well with the production of abundant ascocarps of known biotrophic fungal genera such as Morchella (Buscot and Kottke 1990), Gyromitra, Sphaerosporella, and Tricharina present at our research sites throughout the summer of 1989.…”
Section: Discussionsupporting
confidence: 78%
“…Buscot and Kottke (1990, 1993) and Dahlstrom et al (2000) reported morels could form ectomycorrhizae with Pinaceae plants. Stark et al (2009) speculated morels were associated with orchids, based on evidence obtained through PCR-amplification directly from root-extracted DNA and cloning of the PCR products.…”
Section: Species Distribution and Ecological Diversity Of Morchellamentioning
confidence: 99%
“…Although recent studies suggest that morels can be mycorrhizal (Buscot 1992(Buscot , 1993Buscot and Kottke 1990;Dahlstrom et al 2000), mycologists have until recently classified them as saprobes, which acquire nutrients by breaking down decayed organic matter (Ower 1982). Understanding the distinction between saprobic and mycorrhizal life strategies is critical to establishing appropriate management regimes (Pilz et al 1999).…”
Section: Morel Ecologymentioning
confidence: 99%